Conditional cash transfers increase uptake of and retention in PMTCT care: A randomized controlled trial - Yotebieng, Marcel (Lancet HIV, 2016)
BACKGROUND: Novel strategies are needed to increase retention in and uptake of prevention of mother-to-child HIV transmission (PMTCT) services in sub-Saharan Africa. OBJECTIVE: To determine whether small, increasing cash payments conditional on attending scheduled clinic visits and receiving proposed services can increase the proportions of HIV-infected pregnant women who accept available PMTCT services and remain in care through six weeks postpartum. METHODS: Newly diagnosed HIV-infected women, ≤32 weeks pregnant, were recruited at antenatal care clinics in Kinshasa, Democratic Republic of Congo, and assigned in a 1:1 ratio to an intervention or control group using computer-based randomization. The intervention group received compensation on the condition that they attended scheduled clinic visits and accepted offered PMTCT services ($5, plus $1 increment at each subsequent visit), while the control group received usual care. Outcomes assessed included: 1) retention in care at six weeks postpartum, and 2) to uptake PMTCT services, measured by attendance of all scheduled clinic visits and acceptance of proposed services through six weeks postpartum. Analyses were intent-to-treat. RESULTS: Between April 2013 and August 2014, 612 potential participants were identified, 545 were screened, and 433 were enrolled and randomized. At six weeks post-partum, the proportion of participants retained in care was higher in the intervention group than the control group (174/216, 80·6% vs. 157/217, 72·4%; risk ratio (RR), 1·11; 95% confidence interval (CI), 1·00–1·24). The proportion of participants who attended all clinic visits and accepted proposed services was higher in the intervention group than the control group (146/216, 67·6% vs. 116/217, 53·5%; RR, 1·26; 95% CI, 1·08–1·48). Results were similar after adjusting for marital status, age, and education. CONCLUSIONS: Among newly diagnosed HIV-infected women, small, incremental cash incentives resulted in increased retention along the PMTCT cascade and uptake of available services. The cost-effectiveness of these incentives and their effect on HIV-free survival warrant further investigation.